FLT3 and NPM1 mRNA expression-based risk stratification of de novo acute Myeloid Leukemia - Donghyun Kim; Grerk Sutamtewagul; Yeonhwa Yu (Leukemia Research Reports)
Prognostication of acute myeloid leukemia (AML) at initial diagnosis relies on identification of pre-determined underlying genetic abnormalities. Nevertheless, the disease course of AML remains highly unpredictable and robust reliable prognostic biomarkers for newly diagnosed AML are lacking. We retrospectively explored two publicly available AML RNA-Seq datasets and found that inferior overall survival was associated with high-FLT3 and low-NPM1 transcript levels (“FLT3high/NPM1low”) compared to low-FLT3 and high-NPM1 transcript levels (“FLT3low/NPM1high”) in adult de novo AML patients, with a hazard ratio for death of at least 2. Transcript level-dependent differential overall survival was independent from the underlying FLT3 or NPM1 genotypes. Our two-gene RNA expression-based de novo AML risk stratification may supplement and fine-tune traditional genetic aberration-based prognostication methods.